The effects of local rotation on roll vection induced by globally rotating visual inducer - Nakamura, Shinji (Frontiers in Psychology, 2015)
A visual stimulus rotating globally along an observer’s line of sight can induce the illusory perception of self-rotation in the opposite direction (roll vection). Psychophysical experiments were conducted to examine the effects of local rotations of visual elements of the stimulus that were manipulated independently of the global rotation. The results indicated that the addition of local rotations inconsistent with the global rotation (assumed to be the primary inducer of roll vection), generally decreased the strength of perceived self-rotation. The uniformity of orientation of the elements composing the global visual pattern and the visual polarities assigned to each visual element, i.e., intrinsic directionality concerning up and down, were observed to function as modulators of the effects of the local rotation. These results suggested that local motion signals arising from independent rotations assigned to each element of a visual object cannot be ignored in the perceptual mechanism underlying roll vection.